2016
DOI: 10.1183/16000617.0034-2016
|View full text |Cite
|
Sign up to set email alerts
|

The exposome concept: a challenge and a potential driver for environmental health research

Abstract: Correspondence: Valérie Siroux, Institut Albert Boniot, Inserm/Université Grenoble Alpes U1209, Equipe d'épidémiologie environnementale appliquée à la reproduction et à la santé respiratoire, Rond point de la chantourne, 38706 La Tronche, France. E-mail: valerie.siroux@univ-grenoble-alpes.fr ABSTRACT The exposome concept was defined in 2005 as encompassing all environmental exposures from conception onwards, as a new strategy to evidence environmental disease risk factors. Although very appealing, the exposome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
89
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 21 publications
0
89
0
4
Order By: Relevance
“…Secondly, human beings are subject to a complex multi-exposure to different environmental pollutants that vary over time and space making it difficult to predict the effects of one specific substance on human health [75]. This is the exposome concept [117]. Depending on these combinations, there can be a cumulative, an antagonistic or a synergy of effects that decreases the ability to detect a significant association between an exposure and the effect on POI [27].…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, human beings are subject to a complex multi-exposure to different environmental pollutants that vary over time and space making it difficult to predict the effects of one specific substance on human health [75]. This is the exposome concept [117]. Depending on these combinations, there can be a cumulative, an antagonistic or a synergy of effects that decreases the ability to detect a significant association between an exposure and the effect on POI [27].…”
Section: Discussionmentioning
confidence: 99%
“…The review also draws parallels between the applications of HRMS used in forensic toxicology (Ojanpera et al, 2012, Ibáñez et al, 2014), water quality monitoring (Hernández et al, 2014, Leendert et al, 2015, Gosetti et al, 2016), food safety (Hernández et al, 2011a), and environmental (Petrovic and Barcelo, 2006) and clinical sciences (Yin and Xu, 2014). Suggested additional reading material are the notable review articles on HRMS applications in the ‘omics’ era in general (Madji Hounoum et al, 2016, Ghaste et al, 2016) (Rathahao-Paris et al, 2016) (Schrimpe-Rutledge et al, 2016) and the exposome in particular (Jones, 2016, Athersuch, 2015, Athersuch, 2012, Athersuch and Keun, 2015, Siroux et al, 2016). A large number of reviews on HRMS strategies are found in the literature but none adequately represent studies on characterizing the environmental chemical space in human matrices.…”
Section: Untargeted Analysis Of Biomarkers Of Exposure To Environmmentioning
confidence: 99%
“…The exposome approach is complex, both in term of comprehensively measuring it (hundreds of exposures need to be considered) over the life course and of analysing its relation to health. Despite this, it is likely that a better understanding of environmental factors will lead to improved prevention strategies in asthma [16]. Jørgen Vestbo (Centre for Respiratory Medicine and Allergy, The University of Manchester and University Hospital South Manchester NHS Foundation Trust, Manchester, UK) described three different epidemiological approaches to address scientific questions that cannot be tested in a laboratory, clinical or clinical trial setting.…”
mentioning
confidence: 99%
“…Using a prospective cohort study design and merging data from three cohorts to study the trajectories of lung function decline over 25 years, it was possible to document that maximally attained lung function in early adulthood (small lungs) is probably as important as excess decline in forced expiratory volume in 1 s for the development of COPD. In addition, the beneficial effect of statins on COPD exacerbations was observed using a large nested case-control design [16]. Further details of these approaches are given in accompanying articles in this issue of the ERR [16,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation